2020
DOI: 10.1002/asna.202023773
|View full text |Cite
|
Sign up to set email alerts
|

Smoothed particle inference analysis and abundance calculations of DEM L71, and comparison to SN explosion models

Abstract: We analyze the X‐ray emission from the supernova remnant DEM L71 using the smoothed particle inference (SPI) technique. The high Fe abundance found appears to confirm the Type Ia origin. Our method allows the separation of the material ejected in the supernova explosion from the material swept up by the supernova shock wave. We are able to calculate the total mass of this swept‐up material to be about 228 ± 23 M⊙. We plot the posterior distribution for the number density parameter, and create a map of the dens… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
(29 reference statements)
2
3
0
Order By: Relevance
“…Our tentative Fe Kα detection in DEM L71 falls comfortably within the Type Ia parameter space reported by Y14. This classification is consistent with several previous studies of DEM L71, which identified Fe enhancements and pure-ejecta emission (Ghavamian et al 2003;Hughes et al 2003;Frank et al 2019;Siegel et al 2020a).…”
Section: Discussionsupporting
confidence: 93%
“…Our tentative Fe Kα detection in DEM L71 falls comfortably within the Type Ia parameter space reported by Y14. This classification is consistent with several previous studies of DEM L71, which identified Fe enhancements and pure-ejecta emission (Ghavamian et al 2003;Hughes et al 2003;Frank et al 2019;Siegel et al 2020a).…”
Section: Discussionsupporting
confidence: 93%
“…The total swept-up mass, 𝑀 SW = 𝑛 0 𝑚 p 𝑉 is also estimated to be 𝑀 SW ∼ 145 +30 −25 𝑓 1/2 𝑀 , assuming that the average SNR radius of ∼ 9.7 pc. This calculated mass conforms with the swept-up ISM value given by Siegel et al (2020) within uncertainties. Our estimated explosion energy suggest that DEM L71 originates from a canonical SD or DD progenitor system.…”
Section: Snr Dynamicssupporting
confidence: 86%
“…Optical observations of the Balmer-dominated shock velocities by Ghavamian et al (2003) yield an age estimate of 4, 360 ± 90 yr. Pagnotta & Schaefer (2015) utilized optical images (𝑔 , 𝑟 , 𝑖 , and H 𝛼 ) to identify a great number of possible candidates for the SNs surviving companion; but it has not been detected. Recently, Siegel et al (2020) analyzed the XMM-Newton data of the DEM L71 and estimated the total mass of the swept-up interstellar medium (ISM) as 228 ± 23𝑀 .…”
mentioning
confidence: 99%
“…This method allows us to model the entire remnant and provides significant flexibility while analyzing the emission. Details of the SPI process, combined with a first demonstration of its unique capabilities, were provided in two earlier papers, where it was used to study the SNR DEM L71 (Frank et al 2019;Siegel et al 2020).…”
Section: Application Of Spi To W49bmentioning
confidence: 99%
“…Using the blob volume in the equation for EM above, we derive the combination of n e n H ; we further need a relation between n e and n H to extricate the individual quantities. This process was discussed in Siegel et al (2020). Here we consider two different approaches.…”
Section: Mass and Densitymentioning
confidence: 99%